The, An The Students’ Perception of Remote Teaching: An Analysis of Insufficient Parental Support on Academic Performance - I Gusti Ayu Md Denisha Vedhaswari (Universitas Pendidikan Ganesha, 2022)
The COVID-19 pandemic has urged all the educational communities to transform that was once conventional learning into remote teaching, which has had a significant impact on students' academic performance. Previous observations has been conducted on factors that limited remote teaching. However, some students may perceive a lack of parental support, resulting in negative effects on their academic and emotional outcomes. This study aimed to analyze the impact of insufficient parental support on students' perception of remote teaching and academic performance. This study use a mixed-methods approach. The research respondents and source were only students in the twelve-grade majored in hospitality accommodation from one of the vocational schools.The data were collected with questionnaire and interviews, with purposive sampling technique. The results showed that among other factors of the limitation of remore teaching, the mean score of 3.18 indicated that the statement of students who did not receive sufficient parental support during remote teaching was the highest limiting factor in the remote teaching. Students perceive that when studying at home, if no parental support were present it became one of the barrier to for their academic achievement.